2002
DOI: 10.1046/j.1365-2656.2002.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling state‐dependent interference in common cranes

Abstract: Summary 1.Interference is a key component of food competition, but is difficult to measure in natural animal populations. Using data from a long-term study, we show that interference between common cranes Grus grus L., feeding on patches of cereal seeds, reduces intake rates at high competitor densities, and that the strength of interference is unrelated to food abundance.2. An alternative to measuring interference directly is to predict its strength using behaviour-based models. We test an interference model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 19 publications
1
27
2
Order By: Relevance
“…Apparently, interspecific competition in the bottom patch did not affect individual fish diferentially, by changing their relative competitive ability and aggression, thus the interspecific effect on fish could be revealed at the group level. The lack of crayfish influence on fish aggression does not conform the prediction of individual-based models that aggressiveness should increase with competitors density (Stillman et al, 1997(Stillman et al, , 2002Sirot, 2000). It also does not correspond with studies on competition between fish species that did show interspecific effects on dominance relations within groups, including differential effects on behavioral strategies (Blanchet et al, 2007;Harwood et al, 2002) as well as on brain gene transcription patterns of dominant and subordinate individuals (Roberge et al, 2008).…”
Section: Discussioncontrasting
confidence: 57%
“…Apparently, interspecific competition in the bottom patch did not affect individual fish diferentially, by changing their relative competitive ability and aggression, thus the interspecific effect on fish could be revealed at the group level. The lack of crayfish influence on fish aggression does not conform the prediction of individual-based models that aggressiveness should increase with competitors density (Stillman et al, 1997(Stillman et al, , 2002Sirot, 2000). It also does not correspond with studies on competition between fish species that did show interspecific effects on dominance relations within groups, including differential effects on behavioral strategies (Blanchet et al, 2007;Harwood et al, 2002) as well as on brain gene transcription patterns of dominant and subordinate individuals (Roberge et al, 2008).…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, Stillman et al. () found that in common cranes ( Grus grus ) high‐ranking individuals only engaged in aggressive behavior in environments where their intake fell below a certain threshold. Fewer studies have investigated the environment‐dependent effects of social bonds and kinship on foraging behavior.…”
Section: Introductionmentioning
confidence: 92%
“…However, individuals in many species also show differences in diet preference independent of age or sex (e.g. [4], [5]). Two recent reviews [1], [6] suggested that individual specialization is a widespread but under-appreciated phenomenon.…”
Section: Introductionmentioning
confidence: 99%